(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The rapid development of the globalization process puts a number of specific problems before the culture of the world. This article will analyze exactly the issues of preserving national cultural heritage. Adapting to modern global trends, at the same time, strategies for maintaining a national identity are considered, in particular, ways to promote cultural monuments, folklore and artistic heritage on digital platforms. It will also focus on the issues of comparative analysis of the experiences of different states on the protection of national heritage, the full formation of the socio-cultural younger generation and the strengthening of international cooperation through cultural diplomacy.